The Diagnostic Accuracy of Novel Biomarkers Anti-ApoA-1, Anti-MDA-LDL, and Anti-Osteopontin IgG for Detecting Silent Myocardial Ischemia: Novel Biomarkers Anti-ApoA-1, Anti-MDA-LDL, and Anti-Osteopontin IgG in Myocardial Ischemia - Wang, Zhongqing; Sun, Bin; Wang, Wei; Xiong, Tinglin; Wei, Gang (Journal of Medical Biochemistry, 2026)
Background: Silent myocardial ischemia (SMI) is a significant predictor of adverse cardiac events but remains underdiagnosed. We evaluated the diagnostic accuracy of three autoimmune-inflammation linked biomarkers—anti-apolipoprotein A-1 (anti-ApoA-1) IgG, anti-malondialdehyde-modified low-density lipoprotein (anti-MDA-LDL) IgG, and anti-osteopontin (anti-OPN) IgG—for detecting SMI. Methods: In this cross-sectional study, 210 participants were categorized into three groups: SMI (n=70), stable angina (SA, n=70), and healthy controls (n=70). SMI was defined by exercise-induced ST-segment depression on treadmill testing without symptoms. Serum levels of the three antibodies were measured by enzyme-linked immunosorbent assay. Receiver operating characteristic (ROC) analysis determined the area under the curve (AUC), sensitivity, and specificity. Results: All three biomarkers were significantly higher in the SMI group compared to SA and controls (p<0.001). For SMI vs. controls, anti-ApoA-1 IgG showed an AUC of 0.82 (95% CI 0.75-0.89), anti-MDA-LDL IgG an AUC of 0.78 (0.70-0.85), and anti-OPN IgG an AUC of 0.80 (0.73-0.87). A three-marker panel yielded an AUC of 0.91 (0.86-0.96) with a sensitivity of 87.1% and specificity of 84.3%. Anti-ApoA-1 IgG independently predicted SMI presence in multivariate analysis (OR 3.2, 95% CI 1.8-5.6, p<0.001). Conclusions: Anti-ApoA-1, anti-MDA-LDL, and anti-OPN IgG antibodies are promising biomarkers for SMI, with a combined panel demonstrating high diagnostic accuracy. These findings highlight the potential role of autoimmune-inflammatory pathways in painless myocardial ischemia.